The role of component-resolved diagnosis in Hymenoptera venom allergy. Issue 6 (December 2019) - Bilò, Maria B.; Ollert, Markus; Blank, Simon
Abstract : Purpose of review: Component-resolved diagnostics (CRD) is a new tool aiming at detecting IgE-mediated sensitizations against individual, relevant allergens. Here, we discuss recent literature on molecular diagnosis in the field of Hymenoptera venom allergy (HVA) as well as CRD strengths and weaknesses. Recent findings: CRD, using single molecules or panels of allergens, may discriminate between primary sensitization and cross-reactivity in patients with double/multiple positivity in diagnostic tests with whole extracts, allowing the specialist to choose the most suitable venom for specific immunotherapy (VIT), avoiding unnecessary VIT and reducing the risk of side effects. Future availability of the cross-reactive recombinant pairs of allergens of different species may further increase the diagnostic performance. CRD may be useful in patients with negative allergy tests and a proven history of a previous systemic reaction, including those with mast cell disorders, who could benefit from VIT. In honeybee venom allergy, different sensitization profiles have been identified, which could be associated with a greater risk of VIT failure or treatment side effects. Summary: CRD is undoubtedly an innovative diagnostic method that leads to a more precise definition of the sensitization profile of the HVA patient. Together with a better knowledge of the molecular composition of different venom extracts, CRD may contribute to optimize patient-tailored therapy.